2012
DOI: 10.7455/ijfs/1.2.2012.a5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sponge cake baking in an instrumented pilot oven

Abstract: The quality of baked products is the complex, multidimensional result of a recipe, and a controlled heating process to produce the desired final properties such as taste, colour, shape, structure and density. The process of baking a sponge cake in a convective oven at different air temperatures (160-180-220°C) leading to the same loss of mass was considered in this study. A special mould was used which allowed unidirectional heat transfer in the batter. Instrumentation was developed specifically for online mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…On the other hand, it is known that prolonged exposure to heat and/or to high temperatures can promote the formation of large protein aggregates that can actually be deleterious to digestibility (De Zorzi, Curioni, Simonato, Giannattasio, & Pasini, ; Habiba, ). In our case, we could hypothesize that this resistance to gastric digestion could be due to the presence of pea protein aggregates formed during baking, where cakes undergo temperatures of 200°C at the surface and 100°C at the core (Sommier, Dumoulin, Douiri, & Chipeaux, ). This process leads to the thermal denaturation of the pea globulins and the concomitant generation of high‐molecular‐weight ( M W > 700 kDa) aggregates that may not be accessible by enzymes (Mession, Sok, Assifaoui, & Saurel, ).…”
Section: Resultsmentioning
confidence: 90%
“…On the other hand, it is known that prolonged exposure to heat and/or to high temperatures can promote the formation of large protein aggregates that can actually be deleterious to digestibility (De Zorzi, Curioni, Simonato, Giannattasio, & Pasini, ; Habiba, ). In our case, we could hypothesize that this resistance to gastric digestion could be due to the presence of pea protein aggregates formed during baking, where cakes undergo temperatures of 200°C at the surface and 100°C at the core (Sommier, Dumoulin, Douiri, & Chipeaux, ). This process leads to the thermal denaturation of the pea globulins and the concomitant generation of high‐molecular‐weight ( M W > 700 kDa) aggregates that may not be accessible by enzymes (Mession, Sok, Assifaoui, & Saurel, ).…”
Section: Resultsmentioning
confidence: 90%
“…Here we are focused on the implementation of such sensors for the estimation of both superficial heat exchanges; any other case was excluded. However, other research works have been found regarding the implementation of such sensors in thermal characterization of walls [2,4,11].…”
Section: Experimental Approachesmentioning
confidence: 99%
“…In various thermal engineering fields, the needs of predicting models gradually require a more precise estimation of the real value of the thermal stresses, e.g., superficial heat transfer, absorbed heat flux, to verify the reliability model-measurement when accounting for such thermal stresses. For instance, in the calculations of cooling or heating needs in order to maintain the internal thermal comfort in buildings; in the characterization of walls to determine the incoming and outgoing heat flux through the walls [1,2]; in the estimation of convective and radiative heat transfer in heat exchangers [3]; in the estimation of the convective heat transfer in ovens for drying [4]. In this context, thermal engineers had proposed more than 30 years ago a widely used technique for heat flux measurement able to estimate the heat flux through the surface (conduction), and at the surface (convection and radiation).…”
Section: Introductionmentioning
confidence: 99%